Decrease of Perivascular Adipose Tissue Browning Is Associated With Vascular Dysfunction in Spontaneous Hypertensive Rats During Aging - Kong, Ling-Ran; Zhou, Yan-Ping; Chen, Dong-Rui; Ruan, Cheng-Chao; Gao, Ping-Jin (Frontiers in Physiology, 2018)
Functional perivascular adipose tissue (PVAT) is necessary to maintain vascular physiology through both mechanical support and endocrine or paracrine ways. PVAT shows a brown adipose tissue (BAT)-like feature and the browning level of PVAT is dependent on the anatomic location and species. However, it is not clear whether PVAT browning is involved in the vascular tone regulation in spontaneous hypertensive rats (SHR). In the present study, we aimed to illustrate the effect of aging on PVAT browning and subsequent vasomotor reaction in SHR rats. Herein we utilized histological staining and western blot to detect the characteristics of thoracic PVAT (tPVAT) in 8-week-old and 16-week-old SHR and Wistar Kyoto (WKY) rats. We also detected vascular reactivity analysis to determine the effect of tPVAT on vasomotor reaction during aging. The results showed that tPVAT had a similar phenotype to BAT, including smaller adipocyte size and positive uncoupling protein-1 (UCP1) staining. Interestingly, the tPVAT of 8-week-old SHR showed increased BAT phenotypic marker expression compared to WKY, whereas the browning level of tPVAT had a more dramatic decrease from 8 to 16 weeks of age in SHR than age matched WKY rats. The vasodilation effect of tPVAT on aortas had no significant difference in 8-week-old WKY and SHR, whereas this effect is obviously decreased in 16-week-old SHR compared to WKY. In contrast, tPVAT showed a similar vasoconstriction effect in 8 or 16-week-old WKY and SHR rats. Moreover, we identified an important vasodilator adenosine, which regulates adipocyte browning and may be a potential PVAT-derived relaxing factor (PVRF). Adenosine is dramatically decreased from 8 to 16 weeks of age in the tPVAT of SHR. In summary, aging is associated with a decrease of tPVAT browning and adenosine production in SHR rats. These may result in attenuated vasodilation effect of the tPVAT in SHR during aging.